Solid-state synthesis and process optimization of bone whitlockite. Issue 10 (15th May 2022) - Batool, Sadaf; Hussain, Zakir; Liaqat, Usman; Sohail, Manzar
Abstract: Bone whitlockite (WH) is an important calcium phosphate (CaP) owing to its excellent biological properties. It is the second most abundant bone inorganic phase. A lot of work has been done on other CaPs like hydroxyapatite (HA) and β-tricalcium phosphate (β-TCP) that are easy to synthesize. The synthesis of bone whitlockite is challenging due to its instability in comparison to other CaPs and its synthesis and presence in the body have not been fully acknowledged yet. Synthesis of WH using liquid precipitation method and effect of different parameters on its phase stabilization has been reported earlier. In this study, we are reporting a facile synthesis method for WH using a solid-state reaction. The reaction was carried out by mixing, grinding, and heat-treating the precursors at high temperatures without any medium under the ambient environment. The product obtained was characterized by using x-ray diffraction (XRD), Fourier transforms infrared spectroscopy (FTIR), Raman spectroscopy, Scanning electron microscopy (SEM), and thermogravimetric (TGA) analysis. XRD analysis confirmed that the synthesized material has a whitlockite crystalline phase while FTIR and Raman spectroscopic analysis confirmed the presence of HOP4 2− a peak that is a characteristic of bone whitlockite. The particles synthesized have a size below 50 nm and are stable below 700 ° C. The reported method provides a facile synthetic route for mass production of WH.